Determinación de las propiedades físicas, químicas y orgánicas de tres tipos de suelos (limoso, arcilloso, arenoso) del cantón Rumiñahui, provincia de pichincha para determinar procesos de conservación, periodo 2013 - Ibáñez Aispur, Oliver Israel (2014)
This research was conducted at the Rumiñahui canton located in Pichincha province , with an area of 139 km2, an average altitude of 3500 meters and a population density of 617.64 inhabitants / km ² and UTM coordinates 0 ° 13 'S 78 ° 31'W / -0217, 78,517 Zone 2. The main reason to make this research work was to characterize the environmental soil resources, determination of physical, chemical and three soil organic types (silt, clay, sand) to develop a proposal for environmental management and conservation of soil resources properties, for which one in Rumiñahui Canton was divided into three areas considering their altitude and geographic location by UTM coordinates. Within the analysis made in the chemical properties we determine pH, total N, P, K, equivalent (Ca, Mg, Fe, Mn, Cu, Zn)....